A CLINICAL STUDY ON SAFETY AND EFFICACY OF FORMOTEROL AND TIOTROPIUM COMBINATION COMPARED TO FORMOTEROL AND TIOTROPIUM WITH ROFLUMILAST COMBINATION IN TREATMENT OF MODERATE TO SEVERE CHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS - Devi M, Kavitha; S, Sarumathy; Lal Sasidharan, Sarath; S, Sarumathy; Shaik, Mehanaz; Sandeep, Gottimukkala; Lal Sasidharan, Sarath; Rajasekhar, Vunnam; Shaik, Mehanaz; N, Damodharan; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The objective of this study is to assess the safety and efficacy of formoterol and tiotropium combination compared to formoterol and tiotropium with roflumilast combination in treatment of moderate-to-severe chronic obstructive pulmonary disease (COPD) patients on inhaled combination therapy. Methods: A comparative prospective interventional study was carried out in 61 COPD patients who were visiting the pulmonary medicine ward during 6 months (October 2016 to March 2017). The patients were randomized into two groups. Group A patients received a combination of formoterol and tiotropium, whereas Group B patients received roflumilast along with formoterol and tiotropium combination. Spirometry tests were done to both the study population. Forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC) were noted at the initial visit and after the treatment. All the statistical analyses such as mean and p values were calculated using SPSS 14.0 version software. Results: The average age group of the study population was 57.63Â±8.3 years. Comorbid condition such as diabetes mellitus was higher in the study groups. Comparison of spirometry reports before and after drug administration in both groups was done. FEV1 and FVC were found to be statistically significant between the study group (0.001, p<0.05).The average mean change of FEV1 before and after treatment in Group B was found to be improved as compared to Group B (0.66). Conclusion: Tiotropium and formoterol with roflumilast combination were found to be safe and effective in moderate-to-severe COPD patients.